Comparative study of tissue response to polyglecaprone 25, polyglactin 910 and polytetrafluorethylene suture materials in rats - Nary Filho Hugo; Matsumoto Mariza Akemi; Batista Aline Carvalho; Lopes Luís César; Sampaio Góes Fernanda Costa Grizzo de; Consolaro Alberto (Fundação Odontológica de Ribeirão Preto, 2002)
The authors evaluated the biocompatibility of three suture materials, polyglecaprone 25, polyglactin 910 and polytetrafluorethylene, implanted into subcutaneous tissue in the dorsal region of 20 Wistar albinus rats. After periods of 2, 7, 14 and 21 days, the rats were sacrificed and the specimens were processed for routine histotechnical analysis and stained with hematoxylin and eosin. The rate of fibrosis, angioblastic and fibroblastic proliferation, and also the intensity of inflammation were observed with the optic microscope. The results showed that polyglecaprone 25 suture material induced a mild inflammatory reaction, followed by polyglactin 910 and polytetrafluorethylene, respectively. Such biological behavior must be considered during the selection of the suture material to be used in oral surgery.